Família e sexualidade: o caso da Videira, igreja em células - Rodrigues, Ana Dias Campos (2007)
This work has born of the desire to understand what are the motivation that make the Vineyard Church in Cell´s followers refrain themselves to make sex check out what is the religion offer of that church that maje the followers, prácctice sexual abstinence before marriage. It was made a documentary research, using as a method the phenomenology and socialogical analysis research. The family an marriage concepts have been suffering changes through the years. The family nowadays do not obey the tradicional patriarchal family model anymore, as in the past an the sexuality has been understood as something that is structured by a social way of living, presenting a diversity form. The Vineyard Church in Cell, which is fundamentalist, desires and tries to rescue the traditional patriarchal family model with a sexual abstinence speech and a promotion of a sexuality control it´s objective is to obtain the happiness in marriage struggling against the high level of dissociate families.